578 LONG-TERM OUTCOME OF VENTRICULAR TACHYCARDIA CATHETER ABLATION IN PATIENTS WITH CHRONIC CORONARY TOTAL OCCLUSION. (15th December 2022) - Flore, Francesco; Narducci, Maria Lucia; Niccoli, Giampaolo; Ballacci, Federico; Giordano, Federica; Perna, Francesco; Bencardino, Gianluigi; Montone, Rocco Antonio; Pelargonio, Gemma; Crea, Filippo
Abstract: Background: Chronic coronary total occlusions (CTO) are considered an emerging predictor of ventricular arrhythmias (VAs) but currently there are only few data on arrhythmic outcomes in patients affected by CTO undergoing radiofrequency catheter ablation of VAs. Objective: This study sought to evaluate the impact of unrevascularized CTO on the recurrence of VAs after catheter ablation. Methods: This was a single-center retrospective study that enrolled 120 patients, between 2015 and 2020. All patients were admitted for ventricular tachycardia (VT) or high premature ventricular contractions (PVCs) burden (>25% detected by Holter ECG), without evidence of acute coronary syndrome; they underwent coronary angiography, electrophysiology (EP) study and three-dimensional electroanatomic mapping (3D-EAM) followed by VAs ablation. Results: Twenty-eight patients (23%) of 120 patients showed CTO at coronary angiography. At baseline, CTO group presented with higher prevalence of hypertension, chronic renal disease, systolic ventricular dysfunction, secondary prevention ICD implantation, higher rate of low abnormal activities by 3D-EAM compared to the non-CTO group. At a median follow-up of 15 months (range 1-96 months) after catheter ablation, the only independent predictor of VAs recurrence was the presence of moderate to severe left ventricular (LV) dysfunction (p=0.02). Conclusion: The presence of CTO does not predict VAs recurrence after catheter ablation which is instead predicted by LV dysfunction.